Surface ozone pollution in China: Trends, exposure risks, and drivers - He, Chao; Wu, Qian; Li, Bin; Liu, Jianhua; Gong, Xi; Zhang, Lu (Frontiers in Public Health, 2023)
Surface ozone (O3) is a secondary pollutant produced by photochemical reactions. Long-term exposure to high concentrations of O3 can have adverse effects on human health. Based on high-resolution O3 concentration reanalysis data, we investigated the spatial and temporal patterns, population exposure risks, and dominant drivers of O3 pollution in China from 2013 to 2018 utilizing trend analysis methods, spatial clustering models, exposure-response functions, and multi-scale geographically weighted regression models (MGWR). The results show that: the annual average O3 concentration in China increased significantly at a rate of 1.84μg/m3/year from 2013 to 2018 (p<0.05, R2=0.561). Meanwhile, the increased rate of O3 concentration has a consistent and enhanced positive spatial autocorrelation (p<0.05), with significant hot and cold spot regions. The total population exposed to high O3 concentrations (>160μg/m3) in China increased from 1.2% in 2013 to 28.9% in 2018, and over 20 thousand people suffered premature death from respiratory diseases attributed to O3 exposure each year. Thus, the sustained increase in O3 concentrations in China is an important factor contributing to the increasing threat to human health. Furthermore, the results of spatial regression models indicate that population, the share of secondary industry in GDP, NOx emissions, temperature, average wind speed, and relative humidity are important determinants of O3 concentration variation and significant spatial differences are observed. Our research results have important implications for the implementation of O3 control policies for sustainable development and prevention of population hazards in China.